Purchasing patterns among Afrikaners in greater Cape Town : a study of the effect of environment on economic behaviour - Van der Merwe, A. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Com.) -- University of Stellenbosch, 1963.